Comparison of passive warming with heat-band versus resistive heating blanket for prevention of inadvertent perioperative hypothermia in laparotomy for gynaecologic surgeries - Wan Muhd Shukeri, Wan Fadzlina (2015)
Introduction: Inadvertent perioperative hypothermia (IPH) (defined as core body temperature <35.5°C) is still a common problem despite advancement in a variety of warming systems. In our centre, a common approach to patient warming is by resistive heating blanket, a costly device. To find a cost-effective alternative to patient warming, a group of local researchers innovated a new passive warming device called Heat-Band. We compared the efficacy of the Heat-Band with resistive heating blanket in preventing IPH and its complications during laparotomy for gynaecologic surgeries. Methods: Thirty-two patients undergoing laparotomy for gynaecologic surgeries under combined general-epidural anaesthesia, with expected duration of surgery between two to four hours, were randomized to receive either Heat-Band or resistive heating. In both groups, the warming devices were applied immediately after placement of epidural catheter and induction of general anaesthesia. Core body temperatures measured at several perioperative timepoints in the two groups were compared. Time to extubation, incidence of post-anaesthesia shivering and intraoperative blood loss were also measured and compared between groups. Results: There was no significant difference between the two groups in terms of demographic, anaesthesia and surgical details. The core body temperatures were comparable between the two groups at preoperative period, immediately after induction of anaesthesia, skin incision, one hour after incision, complete skin closing, at extubation, upon arrival to recovery, and one hour postoperatively. There were also no significant differences between the two groups in terms of time to extubation, incidence and intensity of post-anaesthesia shivering and intraoperative blood loss. Neither device failures (as indicated by patients who developed IPH in recovery) nor incidence of adverse effects from warmer usage have been reported in both groups. Conclusion: Heat-Band results in comparable maintenance of core body temperature with the resistive heating in the perioperative period of laparotomy for gynecologic surgeries. It also results in comparable recovery from anaesthesia, incidence of shivering and intraoperative blood loss with the resistive heating. We concluded that Heat-Band is a cost-effective alternative to active warming during anaesthesia and surgery of intermediate duration.